Contribuições ao estudo da secagem em um leito pneumático vertical - Narimatsu, Cristiane Pirola (Universidade Federal de São Carlos, 2004)
Pneumatic dryers are widely applied in industry, mainly because the transport of particulate material can be performed simultaneously with heating and drying operations. However, the design of such equipment is still based on empirical knowledge and fundamental researches on drying still need further development because few experimental works in literature focus simultaneously the momentum, heat and mass transfer mechanisms involved during a drying process. Therefore, the purpose of this work is to analyze the fluid dynamic and thermal behavior in a vertical pneumatic bed by carrying out experimental investigation and analyzing the variables and parameters involved in the process through correlations available in literature and mathematical models, aiming to contribute for a better understanding of the drying phenomena. In the tests was employed a drying bed made of galvanized iron with diameter of 53.4mm, length of 4.1m. The solids are fed into the tube by a gravitational feeder. The experimental data were obtained for two materials: glass spheres (flat surface and non porous structures) and alumina particles (wrinkled surface and porous structures), both with mean diameter of 3.68mm. From experimental results, it was possible to check the operational behavior of the solids feeder, to estimate the fluid-wall attrition coefficient and to identify the flow regimes by locating the dilute and dense phase regions in curves of pressure gradient versus air velocity. The thermal analysis was accomplished by measuring gas and solids temperature profiles and also by solving the energy balances applied to solid and fluid phases. Therefore, it was possible to compare the experimental and theoretical profiles of gas and solids temperatures and also to determine the gas-solid heat transfer coefficient under different conditions of solid flow rates and air velocity. A comparison between the heat transfer coefficient and pressure drop versus air velocity curves shows that the gas-solid heat transfer coefficients are higher in the transition between the dense and dilute regimes. Concerning the investigation of drying in pneumatic beds, it was observed that it is very difficult to measure precisely the local values of gas and solid moistures and the solids temperature, mainly at dilute flow conditions. Through the simulation of one-dimensional mathematical models from Rocha (1988) and Pelegrina and Crapiste (2001) it was verified that the theoretical profiles of gas and solids temperature and moisture are strongly dependent on the correlations used for estimation of heat transfer coefficients. It can be concluded that further studies on the drying in pneumatic beds require the improvement of experimental techniques and the development of new methodologies aiming the validation of models.
Keywords: Sistemas particulados; Leito pneumático vertical; Modelagem matemática; Fluidodinâmica; Calor - transmissão; Partículas; ENGENHARIAS::ENGENHARIA QUIMICA